An improved timestamp-based password authentication scheme with two-party verification using smart cards - Pathan, Al-Sakib Khan; Hong, Choong Seon (2007)
With the recent proliferation of distributed systems and networking, remote authentication has become a crucial task in many networking applications. Various schemes have been proposed so far for the two-party remote authentication; however, some of them have been proved to be insecure. In this paper, we propose an efficient timestamp-based password authentication scheme using smart cards. We show various types of forgery attacks against a previously proposed timestamp-based password authentication scheme and improve that scheme to ensure robust security for the remote authentication process, keeping all the advantages that were present in that scheme. Our scheme successfully defends the attacks that could be launched against other related previous schemes. We present a detailed cryptanalysis of previously proposed Shen et. al’s scheme and an analysis of the improved scheme to show its improvements and efficiency.